2008
DOI: 10.1002/chir.20591
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism of tocopherols versus tocotrienols

Abstract: Vitamin E is an essential nutrient of still increasing economic importance. Vitamin E derivatives include many nonracemic chiral compounds whose chirooptical characterization is scarcely described in the literature. We report the CD spectra of delta-tocopherol and its unsaturated analog delta-tocotrienol. TDDFT calculations demonstrate that the weak CD of delta-tocopherol is determined by the helicity of dihydropyrane ring. In addition, the moderate CD of delta-tocotrienol is due to the exciton interaction bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…The data highlights the correspondence between the absorbance band and the measured molar ellipticity. Mazzini et al reported the CD spectra of δ -tocopherol and tocotrienol homologues, as well as garcinoic acid ( δ -tocotrienolic acid) in methanol in the near and medium UV range [17], and our spectra from dToc in methanol are in good qualitative agreement (discussed further below).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…The data highlights the correspondence between the absorbance band and the measured molar ellipticity. Mazzini et al reported the CD spectra of δ -tocopherol and tocotrienol homologues, as well as garcinoic acid ( δ -tocotrienolic acid) in methanol in the near and medium UV range [17], and our spectra from dToc in methanol are in good qualitative agreement (discussed further below).…”
Section: Resultssupporting
confidence: 76%
“…Calculations by Mazzini suggest this to be the 1Lnormala chromane band; however, they claim it is below the larger 1Bnormalb band. Although it does seem to be present in their dToc/methanol data, it does not play a significant role in the much larger tocotrienol signal, and therefore Mazzini et al do not focus on it [17]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The discrepancy observed for the first CD band at 350-450 nm is not uncommon for aromatic π-π* 1 L b -type transitions. [14][15][16] Thus, the absolute configuration of 1 is (1ЈS,2ЈR,3ЈS,4ЈR)-1. As the CD spectrum of 5 is nearly identical to that of 1 ( Figure S2), the absolute configuration of 5 [17,18] is also assigned as (1ЈS,2ЈR,3ЈS,4ЈR)-5.…”
Section: Resultsmentioning
confidence: 96%